Characteristics of Carcass and Marbling Score of Male Bali Cattle Using Herbal Supplement of Molasses Block Based on Fermented Pineapple Peel - Bulkaini, Bulkaini; Djoko Kiswolro; Fahrullah, Fahrullah; Sumadi, I Ketut; Nazir, Novizar (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Bali cattle are well-adapted to tropical climates and produce stable, standard-compliant carcasses. This study evaluated carcass traits and marbling scores in nine male Bali cattle (206–245 kg) fed with herbal molasses block (HMB) supplements containing fermented pineapple peel. The cattle were randomly assigned to three dietary treatments (3 replicates each) in a Completely Randomized Design:The research material consisted of: Nine male Bali cattle weighing 206-245 kg, concentrate composed of local ingredients, including: pineapple peel fermented with lactic acid bacteria, ground corn, rice bran, molasses and HMB. Nine Bali cattle were placed in individual pens Randomly Based on a Completely Randomized design with 3 treatments and 3 replications. Feeding treatment: P0 = 39% Ground corn + 61% rice bran + 0% fermented pineapple peel + field grass (adlibitum); P1 = 15% ground corn + 65% rice bran + 20% fermented pineapple peel LAB + field grass (ad libitum) and P2 = 12% ground corn + 73% rice bran + 15% pineapple peel without lactic acid bacteria fermentation + field grass + HMB (adlibitum). The research variables consisting of carcass characteristics and marbling scores were analyzed using analysis of variance using the SPSS version 25 program. The results of the study showed that the addition of pineapple peel without lactic acid bacteria fermentation of 15% in the ration and herbal molasses block (P2) produced carcasses of 52.34% significantly (P>0.05) higher than carcasses in P0 (50.55%) and P1 (49.70%). Carcass length ranges from 144.50±0.50-155.50±4.50 cm. The meat index ranges from 0.89 to 0.98. The area of the rib eye ranged from 28.50-33.00 cm2 and was not significantly different (P>0.05) between treatments. The marbling score of male Bali beef based on treatment was 1.81. The use of fermented pineapple peel in the form of HMB can improve the quality characteristics of Bali male cattle carcasses with a carcass percentage reaching 52.34%; carcass length 155.50 cm, meat index 0.89 and rib eye area 28.50 cm2. The resulting meat has a relatively low marbling score, bright meat color with white meat fat. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and Production